2010
DOI: 10.1371/journal.pone.0009633
|View full text |Cite
|
Sign up to set email alerts
|

The RGD Domain of Human Osteopontin Promotes Tumor Growth and Metastasis through Activation of Survival Pathways

Abstract: BackgroundHuman osteopontin (OPN), a known tumor associated protein, exists in different isoforms, whose function is unclear. It also possesses a RGD domain, which has been implicated in diverse function. Here, we use genetic approaches to systematically investigate the function of the RGD domain in different OPN isoforms on tumor progression and metastasis for 2 different solid tumor models.Methodology/Principal FindingsUsing isoform-specific qRT-PCR, we found that OPN-A and B were the main isoforms overexpre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
35
1
5

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(44 citation statements)
references
References 62 publications
(71 reference statements)
3
35
1
5
Order By: Relevance
“…As previously reported on the distinct adhesive properties of murine osteopontin that result from cell specific post-translational modifications, 38 we show that iSPP1 and sSPP1 are differentially expressed by tumor cells, with the former preventing TRP53 stabilization and apoptosis, and the latter signaling to host CCR2 receptors via CCL2 to promote lung homing. Our results corroborate previous work on the inhibition of apoptosis 39 and the involvement of TRP53 in iSPP1-dependent anti-apoptotic signaling 40 and show for the first time that the pro-survival effects of osteopontin in cancer cells are conditional on wild-type TRP53. Our findings imply that targeting of human iSPP1 in clinical trials may be selectively effective against TRP53 wild-type tumors and provide a rationale for stratification of patients by TRP53 status.…”
Section: Discussionsupporting
confidence: 91%
“…As previously reported on the distinct adhesive properties of murine osteopontin that result from cell specific post-translational modifications, 38 we show that iSPP1 and sSPP1 are differentially expressed by tumor cells, with the former preventing TRP53 stabilization and apoptosis, and the latter signaling to host CCR2 receptors via CCL2 to promote lung homing. Our results corroborate previous work on the inhibition of apoptosis 39 and the involvement of TRP53 in iSPP1-dependent anti-apoptotic signaling 40 and show for the first time that the pro-survival effects of osteopontin in cancer cells are conditional on wild-type TRP53. Our findings imply that targeting of human iSPP1 in clinical trials may be selectively effective against TRP53 wild-type tumors and provide a rationale for stratification of patients by TRP53 status.…”
Section: Discussionsupporting
confidence: 91%
“…In addition to the direct function of OPN on tumor cells, 20 we demonstrate for the first time that the OPN expressed by tumor cells can regulate immune cell activation. By coculture system, we found that supernatant from tumors overexpressing OPN significantly inhibited the proinflammatory cytokine TNF-a and increased anti-inflammatory IL-10 levels from monocytes ( Figure 3).…”
Section: Discussionmentioning
confidence: 74%
“…Courter et al have shown that the overexpression of either OPN-a or OPN-b promoted local tumor growth and lung metastasis in SCID mouse xenografts. 20 However, in that study, they did not examine the function of OPN-c. Most recently, it has been reported that OPN-c specifically activated ovarian tumor cell proliferation, migration, invasion, anchorage-independent growth and tumor formation in vivo.…”
Section: Discussionmentioning
confidence: 96%
“…Ovarian malignant transformation is caused by genetic modifications that disrupt the regulation of proliferation, programmed cell death and senescence, but the specific genetic pathways involved in these processes are poorly understood (34,35). Alternative pre-mRNA splicing is an important molecular mechanism associated with tumorigenesis and cancer progression (36) and has been shown to be one of the mechanisms by which cancer cells alter the structure and function of OPN (16)(17)(18)(19)37). Based on these assumptions, we believe that describing the functional significance of OPN splicing isoforms in ovarian cancer would improve the understanding of signaling pathways involved in the progression of this complex neoplasic disease.…”
Section: Discussionmentioning
confidence: 99%